Le Saint Julien de Flaubert – une poétique du vitrail narrativisé - Sabine Narr (Les Dossiers du GRIHL)
Hagiographies exert a lively fascination during the 19th century and are vividly rewritten by many French authors such as Flaubert. The article examines the circumstances of this active and creative ‘reception’. In a close-reading of extracts of Flaubert’s La Légende de saint Julien l’Hospitalier it is shown how the Rouen church window becomes a central basis for the text. It illustrates that intermediality is a fundamental and poetic concept for the legend in 19th century France.